Sosialisasi dan Pendampingan UMKM Mengenai Strategi Digital Marketing di Desa Musir Lor, Kabupaten Nganjuk - Abyansyah Hayyu Sarwono; Daffa Samdya Adabi Selay; Syahrie Ramadhan; Sulastri Irbayuni (Pusat Riset dan Inovasi Nasional, 2023)
Micro, Small and Medium Enterprises (MSME) are one of the activities that can support increased development, movement and development of economic stability. Digital Marketing is an action that aims to reach consumers and potential customers in a timely and fast manner, by marketing and promoting a product or brand through the internet or digital world. With the socialization and mentoring program regarding digital marketing that has been implemented, it has had quite a positive impact on MSME actors, namely a better understanding of how to practice the elements of successful digital marketing, namely branding and rebranding, such as examples of attractive product photos as product sweeteners for increasing interest in buying potential consumers, and making a logo design as a business identity in order to make it easier for the public to recognize the origin of products, as well as packaging that is current and in accordance with the conditions of the products being sold in order to maintain product quality